STUDI LITERATUR: PENGARUH PENGGUNAAN LKPD BERBASIS ELEKTRONIK MENGGUNAKAN PENDEKATAN STEM UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 PESERTA DIDIK - Wedy, Zahra Salsabila; Desnita, Desnita (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This study was conducted to determine the effect of using electronic-based LKPD using the STEM approach to improve students' 21st century skills. The research uses literature reviews by analyzing and looking at the effectiveness of the use of electronic-based LKPD using a STEM approach to 21st century learners' skills. Considering the outcomes of the literature review of 40 articles obtained from searches on google schoolar obtained it is discovered that this approach makes a noteworthy contribution in meeting the needs of more dynamic and interactive learning. Physics LKPD using the STEM approach shows the importance of presenting learning materials with relevant contexts, encouraging students to think critically, creatively, communicatively and collaboratively about the application of physics in everyday life from articles that have been obtained from goole schoolar. So one might argue that the utilization of electronic -based LKPD using the STEM approach can enhance pupils' 21st century abilities.